Integration of Multiple Intelligences in Thematic Instructional Kit in Elementary School - Widiana, I Komang; Sudarma, I Komang; Dibia, I Ketut (International Journal of Elementary Education, 2021)
The learning carried out in schools has been dominated by the development of logic-mathematics intelligence. In fact, every student has various kinds of intelligence called multiple intelligences. This study aims to develop thematic instructional kit oriented to multiple intelligences. This research is a development research (R&D) which adapts the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The instructional kit products developed in this study are in the form of a Lesson Plan (RPP) and Student Worksheets (LKPD). In this study, the product development validity test was only limited to the expert validation test stage. Data were collected using expert validation sheets. The results of research and development show that based on the results of the expert validity test that has been carried out, the average score of expert judgment is 4.88 for RPP products with very good categories, and 4.80 for LKPD products with very good categories. Based on these results, it can be concluded that the instructional kit products developed have good validity and quality to be applied in elementary schools.